Transformasi Limbah Organik Menjadi Produk Bernilai Tambah: Pengembangan Sabun Cair Ramah Lingkungan - Riana Septiani; Susanti Sundari (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
XX has been carrying out sanitation operations using soap sold on the market, which is made from chemicals and is not environmentally friendly. Chemical soap can have an impact on water pollution because the chemicals are difficult to decompose and can disrupt aquatic ecosystems and harm living creatures in them. Plus, managing chemical soap waste also requires additional costs for the company. This research is a continuation of previous studies which aimed to develop environmentally friendly products, with a focus on developing eco-enzyme based liquid soap. This research method is an experiment in the field to test theories or develop products, by applying the Cold Process method in making antiseptic liquid soap. The results of this research show that liquid soap from eco-enzyme has great potential as an environmentally friendly alternative for cleaning and is effective in inhibiting the growth of E. coli bacteria, and the organoleptic test shows that the majority of respondents gave positive responses, with 66.7% stating the color of the soap is attractive, 66.7% assessing the aroma as very good, 50% stating the cleaning quality is very good, and 46.7% assessing the amount of foam in the good category. From an economic perspective, there is a 32% cost savings from substituting liquid soap on the market with eco-enzyme liquid soap.